2009
DOI: 10.1038/ajh.2009.132
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Microalbuminuria With Aortic Stiffness Is Independent of C-Reactive Protein in Essential Hypertension

Abstract: Our results suggest that in patients with essential hypertension, MAU and CRP are independently associated with an increased aortic stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 41 publications
0
28
2
1
Order By: Relevance
“…Moreover, most participants did not have significant renal dysfunction (mean estimated glomerular filtration rate 65.4 ml/min/1.73 m 2 ). Differently from our study, an association between the UACR and arterial stiffness was reported in previous studies that included mainly diabetic patients (38) or untreated hypertensive patients (8,11,36). …”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Moreover, most participants did not have significant renal dysfunction (mean estimated glomerular filtration rate 65.4 ml/min/1.73 m 2 ). Differently from our study, an association between the UACR and arterial stiffness was reported in previous studies that included mainly diabetic patients (38) or untreated hypertensive patients (8,11,36). …”
Section: Discussioncontrasting
confidence: 99%
“…Although an association between arterial stiffness and microalbuminuria was previously reported (8,11,35,36), we were unable to confirm this in our study. Because a reduction in aPWV resulting from antihypertensive treatment has been shown to decrease the UACR (37), the lack of association may be because the participants in our study had a low UACR (mean = 8.2 mg/g, normal <30 mg/g), their blood pressure was, in general, well controlled, and nearly a third of participants were being treated with either angiotensin-converting enzyme inhibitors or angiotensin receptor blockers, drugs known to decrease microalbuminuria.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Previous studies exploring similar issues 7,21 analyzed a sample size similar to this study. Descriptive analysis was performed for qualitative variables and quantitative results are presented as mean ± standard deviations.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that arterial stiffness parameters predict clinical outcomes, such as coronary artery disease 5,6 , stroke 6 , urinary albumin excretion 7,8 , progression of chronic kidney disease 9 , survival in end-stage renal disease 10 and general cardiovascular risk 11 . The current standard for assessing this condition involves the measurement of several variables by noninvasive applanation tonometry, including the radial augmentation index (r-AI) 12 .…”
Section: Introductionmentioning
confidence: 99%